PMO-110 An audit of pancreatic cancer outcomes in the district general hospital setting: outcomes appear better than national average. (28th May 2012) - Akbar, T; Murphy, F
Abstract : Introduction: Pancreatic cancer outcomes nationally demonstrate poor survival outcomes with 1 and 3-month survival rates of 73% and 47%. We performed an audit of our experience of our patients with pancreatic cancer in the setting of a district general hospital and compared our results with the national dataset. Methods: We carried out data search from our system with all patients with a new diagnosis over 16 months from June 2010 to October 2011. The information was correlated with case notes and relevant histology and radiology reports. The data were collected and entered on an Excel spreadsheet for analysis. Results: 21 new diagnoses with a mean age of 73, range from 56 to 95. The male to female ratio was 3:2. The most common presenting symptoms were jaundice and abdominal pain. The average duration of symptoms developing to being seen was approximately 70 days. Patients on average had a CT scan within 7 days of being seen in clinic. Range 1–29 days. The most common radiological diagnosis was head of the pancreas tumour; representing 52% of cases. 62% of patients had biliary obstruction of which 69% had an ERCP and 31% had PTC insertion of a stent. The stent was changed at least once in 38% of these patients. 14% of patients had duodenal obstruction. 19% of patients underwent Whipples procedure with 57% patients having chemotherapy. Gemcitabine/Cisplatin combination was most commonly used. 48% of patients had died with a mean of 154 days from when they were first seen. The range was 80–226 days. 75% of the patients who had Whipples procedure and post op chemotherapy had metastatic disease on CT on average 10 months later. Of those that are still alive, only one other than those that had the Whipples procedure had survived more than a year. Conclusion: Our data demonstrated that our outcomes were better than the national data set produced by the Pancreatic Cancer UK charity. The average 1-year survival is 16% and our figures show that 24% of our patients survived more than 1-year. Our cumulative survival at 1-month and three months was comparable to the national average (100% and 86% vs 74% and 47%), are patients have radiological diagnosis sooner and more of our patients go on to have surgery. Our survival data supports that as a district general hospital we are able to manage patients' pancreatic cancer effectively and safely with good outcomes. Competing interests: None declared.